2023
DOI: 10.1021/acsanm.3c01442
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning and Silver Nanoparticle-Based Surface-Enhanced Raman Spectroscopy for Classification of Cardiovascular Disease Biomarkers

Katelyn Dixon,
Raissa Bonon,
Felix Ivander
et al.

Abstract: Characterizing complex biofluids using surface-enhanced Raman spectroscopy (SERS) coupled with machine learning (ML) has been proposed as a powerful tool for point-of-care detection of clinical disease. ML is well-suited to categorizing otherwise uninterpretable, patient-derived SERS spectra that contain a multitude of low concentration, disease-specific molecular biomarkers among a dense spectral background of biological molecules. However, ML can generate false, non-generalizable models when data sets used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Evidence indicates that these NPs cause defective ubiquitination autophagosome-lysosome fusion at the subcellular level [82]. Future, in-depth studies on the genotoxicity of AgNPs and their potential role in cancer are now of interest, as evidenced by multiple studies [83]. Interestingly, although some research contends that these particles mainly spare the blood-brain barrier (BBB) from toxicity, other reports found that administering AgNP altered the BBB's permeability, providing a fascinating potential avenue for future applications [15].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Evidence indicates that these NPs cause defective ubiquitination autophagosome-lysosome fusion at the subcellular level [82]. Future, in-depth studies on the genotoxicity of AgNPs and their potential role in cancer are now of interest, as evidenced by multiple studies [83]. Interestingly, although some research contends that these particles mainly spare the blood-brain barrier (BBB) from toxicity, other reports found that administering AgNP altered the BBB's permeability, providing a fascinating potential avenue for future applications [15].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%